Development of Teaching Materials in the Subject of Morals through the Educative Communication Model - Iip Latifah; Naf'an Torihoran; Muhajir (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to develop teaching materials in the subject of aqidah morals through an educative communication model at Madrasah Aliyah Raudhatul Ulum Anyer. Research using R&D development research. This method is used to produce certain products, and test the effectiveness of these products. Based on the research and discussion that has been described, the researcher can conclude that the development of teaching materials in the Aqidah Akhlak subject through an educative communication model on ethics in behavior has been successfully developed through research procedures based on the R&D development model and referring to research steps according to Borg and Gall which is simplified into five stages, namely: research and data collection, product design (determining and collecting materials, preparation and development of teaching materials, determining images and written text, merging, interactive aspects and finishing), design validation, media and materials validated by their respective experts, product revisions and finally product trials. Then for the effectiveness of the animation shown in the final stage, namely product trials by means of students filling out questionnaires and tests on Google forms, developing teaching materials in the Akidah Akhlak subject through this educative communication model gets scores from students with an average of 6 in the category